The Reformation its roots and its legacy - Berthoud, Pierre; Lalleman, Pieter J.; Selderhuis, Herman J. (Eugene : Wipf and Stock Publishers, 2017)
The papers in this volume are less a commemoration of the Reformation than a discussion of its meaning in the era after 2017. What is celebrated in 2017 is not the Reformation as such, but the beginning of the Reformation. It was the dynamics of the ""new"" theology of Luther and Calvin that caused a radical change with global effects. Reformation is not just an historical event but an ongoing movement of renewal and change. The message of the Reformation constantly challenges us to think through positions, actions, attitudes, and programs.This book presents contributions from eleven experts f.
Includes bibliographical references.
Description based upon print version of record.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Reformation; Theology -- History -- 16th century; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books